Recent advances in organic solar cells research in Mexico. - Salinas-García, I.U.; Castro-Carranza, A.; Vázquez, A.; Olivos-Lagunes, E.; Nolasco, J.C. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2025)
Due to the growing demand in the energy sector, alternative energy sources have been proposed instead of fossil fuels. Solar energy is produced mostly by crystalline silicon solar cells. Despite this, a new technology has emerged in recent years, organic solar cells (OSCs). These cells have advantages over silicon ones such as their low cost and their ability to be manufactured on flexible substrates. Their general composition is based on a photoactive layer surrounded by two electrodes and charge transporting buffer layers. At present, the efficiency achieved by these devices reaches up to 18%; however, OSCs still have to face challenges such as the degradation of their components due to thermal and photochemical factors. On the other hand, Mexico has a great potential to harness solar energy, even more than countries as England or Germany. In Mexico there is also a wide line of research in the field of OSCs reporting up to 25 papers published since 2018. In this work, a review is going to be made about the advances in OSOs in the areas of: synthesis of new materials for active layers, transport layers, contact improvement, simulation, degradation studies and characterization of interfaces. It was found the maximum efficiency reached by Mexican researchers was 10.85%. On the other hand, new proposals for the active layer with small molecules and ferrous nanoparticles were mentioned. In the case of transport layers, graphene derivates and nanoparticles were used. Regarding the simulation field, phenomena present in OSCs active layers were studied. For this purpose, software programs such as Silvaco/ ATLAS TCAD and Afors-HET were mentioned. Finally, the most used material characterization methods in organic solar cells are addressed.